Indutores de resistência no manejo pós-colheita da antracnose em manga ‘Tommy Atkins’ - Nunes, Maria Silvana (2021)
One of the biggest problems of fruit growing today is the residue left by the use of large amounts of pesticides, compromising human, animal and environmental health. Thus, organic food is gaining more and more appreciation from consumers, as it is produced in a safer and more sustainable model of agriculture. The objective of the work was to evaluate the influence of resistance inducers in the postharvest management of anthracnose and the physical-chemical and enzymatic changes caused in 'Tommy Atkins' mangoes produced in a conventional cultivation system and in a period of conversion to the organic system. The experiments were conducted at the Laboratory of Phytopathology, of Universidade Federal da Paraíba. The treatments used were: T1- Agro-Mos®, T2- Bion 500 WG®, T3- Kaolin, T4- Ecolife®, T5- Eco-Shot®, T6- Pro-Agrim®, T7- Rocksil®, T8- Control and T9- Tiabendazole fungicide. The severity of anthracnose was evaluated, observing the natural infection using a scale of grades. The analyzes of firmness, pH, vitamin C, soluble solids, titratable acidity and SS / AT ratio were performed on the 3rd, 6th, 9th and 12th day of storage and the assessment of fresh weight loss was determined daily. The enzymatic activity of Peroxidase, Polyphenoloxidase and Phenylalanine ammonia lyase was determined in the peel of the fruits through spectrophotometry. The experiment was conducted in a completely randomized design in a split plot scheme. The data were subjected to analysis of variance, the means were compared by the Scott-Knott test (p ≤ 0.05) between treatments and subjected to regression analysis between the storage periods. The results of the evaluation of the severity in conventional mangoes showed that the use of Kaolin and Rocksil® provided, proportionally, a reduction of 8.1% and 11.3% of the severity determined in Control treatment mangoes. The application of Kaolin, Eco-shot® and Rocksil® were the treatments with potential elicitor in the enzymatic activity of the fruits. For mangoes in conversion period, all treatments were effective in reducing the severity of anthracnose. No eliciting action was identified under the enzyme Polyphenoloxidase and the treatment with Rocksil® was the most efficient in stimulating the enzymatic activity of Phenylalanine ammonia lyase. The physical-chemical characteristics were not compromised with the application of the elicitor treatments tested in this study on mangoes from conventional cultivation systems and in a period of conversion to the organic system. The elicitors Caulim, Ecolife® and Rocksil® showed high potential as more sustainable alternatives in the management of anthracnose in mangoes from the conventional cultivation system. For mangoes produced in a period of conversion to the organic system, the use of Rocksil® is an alternative to conventional treatment with the use of chemical fungicide.